2022
DOI: 10.1017/aaq.2021.157
|View full text |Cite
|
Sign up to set email alerts
|

A New Radiocarbon Database for the Lower 48 States

Abstract: From 2014 to 2020, we compiled radiocarbon ages from the lower 48 states, creating a database of more than 100,000 archaeological, geological, and paleontological ages that will be freely available to researchers through the Canadian Archaeological Radiocarbon Database. Here, we discuss the process used to compile ages, general characteristics of the database, and lessons learned from this exercise in “big data” compilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Over the last two decades, archaeologists have invested considerable time, resources, and effort in aggregating large radiocarbon databases, allowing us to better address the problem of random sampling error (Rick, 1987; Williams, 2012; Brown, 2015, 2017; Fitzhugh et al, 2016; Crema et al, 2016, 2017; Robinson et al, 2019; Kelly et al, 2021; Price et al, 2021; Shennan and Sear, 2021; Crema, 2022). These efforts to aggregate and archive data in digital repositories and targeted attempts to compile archaeological radiocarbon databases at up-to-continental scales (e.g., Canadian Archaeological Radiocarbon Database /CARD: ; Kelly et al, 2021; Palmisano et al, 2022) have made it possible to compile TFDs of dates for many regions of interest. The present study benefits from the availability of such radiocarbon databases, drawing on large samples of radiocarbon data from Alaska, Hokkaido, and the Kuril Archipelago.…”
Section: Tfd Generation: Methods and Constraintsmentioning
confidence: 99%
“…Over the last two decades, archaeologists have invested considerable time, resources, and effort in aggregating large radiocarbon databases, allowing us to better address the problem of random sampling error (Rick, 1987; Williams, 2012; Brown, 2015, 2017; Fitzhugh et al, 2016; Crema et al, 2016, 2017; Robinson et al, 2019; Kelly et al, 2021; Price et al, 2021; Shennan and Sear, 2021; Crema, 2022). These efforts to aggregate and archive data in digital repositories and targeted attempts to compile archaeological radiocarbon databases at up-to-continental scales (e.g., Canadian Archaeological Radiocarbon Database /CARD: ; Kelly et al, 2021; Palmisano et al, 2022) have made it possible to compile TFDs of dates for many regions of interest. The present study benefits from the availability of such radiocarbon databases, drawing on large samples of radiocarbon data from Alaska, Hokkaido, and the Kuril Archipelago.…”
Section: Tfd Generation: Methods and Constraintsmentioning
confidence: 99%
“… Transactional Databases of Archaeological Science Samples . There are several efforts underway to develop integrated and curated databases of archaeological science samples—for example, radiocarbon dates (Bird et al 2022; Gajewski et al 2011; Kelly et al 2022), tree-ring data (Grissino-Mayer and Frits 1997), obsidian sources (Acquafredda et al 2018; Jones et al 2019; Northwest Research Obsidian Studies Laboratory 2001), ceramics (Berlin 2020; Glascock 2001), and isotopes (Fernandes et al 2021; Plomp et al 2022). To be most effective, these need to be interoperable with repositories containing other data from associated archaeological contexts.…”
Section: Why Fair Practices Are Important In Archaeologymentioning
confidence: 99%
“…al. 2011;Kelly et al 2022), tree-ring data (Grissino-Mayer and Frits 1997), obsidian sources(Acquafredda et al 2018;Jones et al 2019; Northwest Research Obsidian Studies Laboratory 2001), ceramics(Berlin 2020;Glascock 2001), and isotopes(Fernandes et al 2021;Plomp et al 2022). To be most effective, these need to be interoperable with repositories containing other data from associated archaeological contexts.…”
mentioning
confidence: 99%
“…Radiocarbon dates are a good example. Several recent projects have shown that one can learn a tremendous amount regarding human demographic processes simply by compiling a very large number of independently dated events from known spatial locations using the “dates as data” approach pioneered by John Rick (Bird et al 2022; Kelly et al 2022; Rick 1987; Robinson et al 2019; Shennan et al 2013). Radiocarbon dates represent only a very small fraction of the total information collected by archaeologists through field and laboratory work, and they are conceptually quite simple, representing the measurement of a ratio of specific isotopes in an organic sample.…”
Section: Envisioning Data Integration In Crmmentioning
confidence: 99%